The Oxford handbook of offshoring and global employment - Bardhan, Ashok Deo, 1957-; Kroll, Cynthia A.; Jaffee, Dwight M., 1943- (New York ; Oxford : Oxford University Press, 2013)
This text contains essays from around the world addressing how globalization and offshoring have affected employment structure and job creation in both developing and developed countries.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Offshore outsourcing; Labor market